Temporal response of ectopic activity in guinea pig ventricular myocardium in response to isoproterenol and acetylcholine - Greer-Short, Amara; Poelzing, Steven (Frontiers in Physiology, 2015)
Both beta adrenergic and muscarinic receptor stimulation independently potentiate arrhythmogenesis. However, the effect of simultaneous stimulation on arrhythmogenesis is not well known. The purpose of this study was to determine the temporal response of arrhythmia risk to individual and combined autonomic agonists. Guinea pig hearts were excised and Langendorff-perfused. The beta adrenergic receptor and muscarinic receptor agonists were isoproterenol(ISO,0.6μM) and acetylcholine(ACh,10μM) respectively. All measurements with agonists occurred over 21 minutes. ISO induced ectopic activity for the first 8 minutes. ISO also transiently shortened and then prolonged R-R interval over a similar time course. ACh added after ISO transiently induced ectopic activity for 12 minutes, while R-R interval invariantly prolonged. ACh alone produced few ectopic beats, while invariantly prolonging R-R interval. In contrast to ISO alone, ISO following ACh significantly increased ectopic activity and shortened R-R interval for the duration of the experiment. Animals aged 17-19 months exhibited sustained arrhythmogenesis while those aged 11-14 did not. When ACh was removed in older hearts while ISO perfused, a transient increase in ectopic activity and decreased R-R interval was observed, similar to ISO alone. These data suggest that pre-treating with and maintaining ACh perfusion sustains ISO sensitivity, in contrast to ISO perfusion alone.